Combining deep-inspiration breath hold and intensity-modulated radiotherapy for gastric mucosa-associated lymphoid tissue lymphoma: Dosimetric evaluation using comprehensive plan quality indices - Seo Hee Choi; So Hyun Park; Jason Joon Bock Lee; Jong Geol Baek; Jin Sung Kim; Hong In Yoon (Radiation Oncology, 2019)
Abstract Background Although there have been many attempts to increase the therapeutic ratio of radiotherapy for gastric mucosa-associated lymphoid tissue lymphoma (MALToma), only a few planning studies have reported the efficacy of the modern radiotherapy technique till date. Therefore, we performed the dosimetric comparison among 3-dimensional conformal radiotherapy (3D-CRT) and intensity-modulated radiotherapy (IMRT) plans, using deep-inspiration breath hold (DIBH) or free-breathing (FB) techniques, to determine the most optimal plan for gastric MALToma. Methods We evaluated 9 patients with gastric MALToma for whom 3D-CRT, step-and-shoot IMRT (SIMRT), volumetric-modulated arc therapy (VMAT), and tomotherapy plans with identical prescribed doses were generated using DIBH or FB computed tomography (CT). Planning target volume (PTV) coverage and non-target doses were calculated for each plan and compared with plan quality metric (PQM) scores. Results All 72 plans of 9 patients satisfied our dosimetric goals, and the IMRT plans and 3D-CRT plans had similarly good conformity index values with no differences related to respiratory movement. IMRT plans yielded significantly better doses to the organs-at-risk, and DIBH plans yielded significantly lower liver, heart, and lung Dmean and spinal cord Dmax with smaller irradiated volumes compared to FB plans. For the mean PQM scores, VMAT-DIBH and SIMRT-DIBH yielded the best scores, whereas 3D plans provided reduced beam monitor unit values. Conclusion Our findings demonstrate that modern RT technologies (DIBH with VMAT or SIMRT) could potentially provide excellent target coverage for gastric MALToma while reducing doses to organs-at-risk. However, the relevance of the most optimal plan considering clinical outcomes should be confirmed further in a larger patient cohort.